Knowledge of Gestational Diabetes Mellitus Among Diabetic Pregnant Females: Knowledge of Gestational Diabetes Mellitus - Azmat, Saddiqa; Sajjad, Nazia; Asghar, Sadia; Ahmed, Khalil; Anwar, Maria; Ishaq, Hafiza Ayesha (Pakistan Journal of Health Sciences, 2024)
The prevalence of Gestational Diabetes (GDM) is rising quickly and patients require assistance with decision-making, behavioral control and obtaining the knowledge required for self-care. The knowledge of GDM, together with nutritional guidance and glycemic control education, is crucial to the care of diabetic women. Objective: To determine the knowledge among gestational diabetic pregnant females. Methods: A cross sectional study was conducted at obstetrics and gynecology outpatient departments in Department of Obstetrics and Gynecology, Niazi Medical and Dental College, Sargodha. 150 pregnant females aged range (18-40) year, with any gravida and diagnosed with GDM were enrolled in current study. A structured questionnaire regarding the knowledge of gestational diabetes was used to collect data. Data were entered and analyzed in Statistical Package for Social Sciences (SPSS) version 21.0. Results: Majority of participants were 18-30 years 80 (59.3%) old. 42 (28%) were normal weight, 82 (54.6%) were overweight and 26 (17.3%) were obese while 98 (65.3%) women were housewives. 63 participants know about self-care routine of GD, while 58 know about feto-maternal complications. Majority 90 (60%) females don’t know about the risk and symptoms of gestational diabetes. 101 (67.3%) have poor knowledge about glucose monitoring. When they asked about the management of hypo and hyper glycemia 81 (54%) don’t have enough knowledge about management protocols. Regarding the diagnostic procedures 74 (49.3%) have good knowledge. Conclusions: The study concluded that most participants, have lack of knowledge of GDM, management of Gestational Diabetes Mellitus (GDM), its symptoms, fetomaternal complications and diagnostic criteria.